4(4x-3)-6=12z-12-2x

Simple and best practice solution for 4(4x-3)-6=12z-12-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(4x-3)-6=12z-12-2x equation:


Simplifying
4(4x + -3) + -6 = 12z + -12 + -2x

Reorder the terms:
4(-3 + 4x) + -6 = 12z + -12 + -2x
(-3 * 4 + 4x * 4) + -6 = 12z + -12 + -2x
(-12 + 16x) + -6 = 12z + -12 + -2x

Reorder the terms:
-12 + -6 + 16x = 12z + -12 + -2x

Combine like terms: -12 + -6 = -18
-18 + 16x = 12z + -12 + -2x

Reorder the terms:
-18 + 16x = -12 + -2x + 12z

Solving
-18 + 16x = -12 + -2x + 12z

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-18 + 16x + 2x = -12 + -2x + 2x + 12z

Combine like terms: 16x + 2x = 18x
-18 + 18x = -12 + -2x + 2x + 12z

Combine like terms: -2x + 2x = 0
-18 + 18x = -12 + 0 + 12z
-18 + 18x = -12 + 12z

Add '18' to each side of the equation.
-18 + 18 + 18x = -12 + 18 + 12z

Combine like terms: -18 + 18 = 0
0 + 18x = -12 + 18 + 12z
18x = -12 + 18 + 12z

Combine like terms: -12 + 18 = 6
18x = 6 + 12z

Divide each side by '18'.
x = 0.3333333333 + 0.6666666667z

Simplifying
x = 0.3333333333 + 0.6666666667z

See similar equations:

| 60-5x=70-25x | | x(x-6)=14 | | -8x+2=8-6x | | -5(-3w+4)-7w=2(w-9)-5 | | (p^3-4p^2+p)-(3p^2+2p+7)=0 | | 4(a-8)=12a-6 | | 10x-4(x-6)=5x+5 | | 1v+7=13+4v | | -4(5x-6)+2=-20x+26 | | x^3y^4-y^4=0 | | (x+5)(-6)=0 | | -3+d=21 | | 2(v-2)=6v+7-3(-4v-1) | | [2x-4]=9 | | 7x+10=-2x+28 | | 1-1x=-1+1x-5-3 | | 7x+12x=-7-13 | | V=x^2h | | -4=-5v-9 | | 1.75x+2(.375x+4.5)=28.625 | | (-6.4x+6)(-6)= | | -4=(-4m+9m)-13 | | 4h+2=7h-19 | | x^2+y^2+2x-34=0 | | 5t+25-5= | | 3=5k | | X+2z= | | c-7=-14 | | -6.8(2t+5)-2.8(4t-6)= | | c-7=-14 | | -6.8(2t+5)-2.8(4t-6)= | | -6.8(2t+5)-2.8(4t-6)= |

Equations solver categories